A BaO and ZrO based 2 Composite oxide refractory material of the system and preparation method thereof
By using zirconium dioxide and barium carbonate as raw materials, a barium zirconium oxide composite refractory material with BaZrO3 phase and Ba2ZrO4 phase was prepared, which solved the problems of complex process and high cost of existing BaZrO3 refractory materials, achieved stability of the density and chemical properties of the material, and was suitable for the smelting of highly reactive metals.
Patent Information
- Application Number
- CN202410018825.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-01-05
AI Technical Summary
The existing BaZrO3 refractory materials synthesized by barium oxide and zirconia have problems such as complex process, high cost and unstable material in industrial production.
Using zirconium dioxide and barium carbonate as raw materials, a barium zirconium oxide composite refractory material with BaZrO3 phase and Ba2ZrO4 phase was prepared through mixing, molding and sintering processes. This material improves refractory, density and compressive strength by forming a composite barium-containing phase and a composite zirconium-containing phase.
The density and chemical properties of refractory materials are stabilized, the porosity and cost are reduced, the thermal shock resistance and comprehensive performance are improved, and it is suitable for the smelting of highly reactive metals.
Smart Images

Figure HDA0004651847860000011 
Figure HDA0004651847860000012 
Figure HDA0004651847860000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oxide refractory materials, and specifically relates to a composite oxide refractory material based on BaO and ZrO2 system and a preparation method thereof. Background Art
[0002] Oxide refractory materials are refractory products made of high melting point and high purity oxides by high temperature ceramic process or other special process methods. Also known as oxide ceramics, they have many advantages such as good chemical stability, low cost, and easy preparation, and are widely used in various fields such as metallurgy, aerospace, atomic energy and new energy. In the metallurgical industry, oxide refractory materials can be used as linings of high temperature kilns, furnace tubes, crucibles for melting pure metals, alloys or other highly active substances, thermocouple protection sleeves, high temperature heating elements, and oxygen probes for rapid determination of oxygen content in molten steel and furnace gas.
[0003] Barium oxide (BaO) is an alkaline earth metal oxide, white or off-white cubic crystals, with a melting point of 1920°C. Barium is the most active element among alkaline earth metals, so barium is not found in nature, and often exists in the form of barite and witherite (BaSO4). In industry, barium is often used to make barium salts, alloys, fireworks, nuclear reactors, etc., and is also an excellent deoxidizer for refined copper. It is widely used in alloys, including lead, calcium, magnesium, sodium, lithium, aluminum and nickel alloys. Metallic barium can be used as a degasser to remove trace gases from vacuum tubes and picture tubes, and as a degasser for refined metals. In recent years, barium oxide has played an important role in the application of new technologies in the chemical and electronic industries. As an advanced ceramic material, the application of barium oxide in the field of refractory materials is even more promising.
[0004] Zirconium dioxide (ZrO2) has a melting point of 2700°C. It is particularly stable in an oxidizing atmosphere, has strong resistance to acidic and neutral slags, and has good mechanical properties. However, zirconium dioxide is also a phase change material, with three crystal forms at different temperatures: cubic (c), tetragonal (t) and monoclinic (m). The transformation of different phases causes pure ZrO2 to be very unstable and difficult to support dense crucible products alone.
[0005] Patent CN201110350464.1 discloses a BaZrO3 refractory material for titanium and titanium alloy smelting crucibles and a method for preparing the crucible. BaCO3 and ZrO2 are used as raw materials, and barium zirconate (BaZrO3) crystal powder is synthesized by repeated firing at 1200-1400°C; the barium zirconate material is supplemented with an appropriate amount of additives and binders, and is made into a crucible through pretreatment, molding, pre-sintering, sintering and other processes. However, the technology disclosed in the above patent cannot meet the needs of industrial production. The reasons are: (1) Additional materials are required to assist sintering. (2) The sintering temperature and time are relatively long, resulting in a complex process and high cost.
[0006] Excessive BaO will produce hydration in the refractory material, and BaO is easy to volatilize under high-temperature sintering conditions, affecting the strength and stability of BaZrO3 refractory materials. Therefore, in industrial production, the preparation of BaZrO3 refractory materials is usually synthesized by excessive ZrO2 to ensure that BaO can fully react. However, ZrO2 will undergo phase changes with temperature, resulting in structural instability and causing the crucible to break and crack. Summary of the invention
[0007] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a barium zirconium oxide composite refractory material and a preparation method thereof, and to composite two refractory materials containing barium and zirconium to prepare a new type of barium zirconium oxide composite refractory material for use in the smelting of high-activity metals.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] A barium zirconium oxide composite refractory material has a chemical composition of BaO and ZrO2 system. Calculated by molar percentage, the raw material composition ratio is:
[0010] Zirconium dioxide: barium carbonate = 1:1-1:2;
[0011] The barium zirconium oxide composite refractory material is a two-phase coexistence composite phase of BaZrO3 phase and Ba2ZrO4 phase;
[0012] The size of the BaZrO3 phase is greater than that of the Ba2ZrO4 phase;
[0013] The BaZrO3 phase is in an irregular polygonal state, and the Ba2ZrO4 phase is in a spherical particle state.
[0014] In a preferred embodiment of the present invention, the specific size range of the BaZrO3 phase is 3.5-6.0 μm.
[0015] In a preferred embodiment of the present invention, the specific size range of the Ba2ZrO4 phase is 1.0-2.5 μm.
[0016] A method for preparing a barium zirconium oxide composite refractory material comprises the following steps:
[0017] (1) Preparation steps of pre-synthetic material:
[0018] The zirconium dioxide and barium carbonate are mixed to obtain a mixed powder, an organic solvent is used as a ball milling medium, the mixed powder, the ball milling medium and the ball milling beads are added into a planetary ball mill in a mass ratio of 1-2:3-4:3-4, wet ball milling is used for 10-30 hours, and then the ball-milled slurry is dried at 90-100° C. for 18-24 hours, and sieved after drying to obtain a loose powder.
[0019] (2) Preparation steps of barium zirconium oxide composite refractory material:
[0020] The powder of step (1) is pressed into sheets at 12-16 MPa using a tablet press, and then synthesized, and sintered at 1650-1700° C. for 6-8 hours to obtain a barium zirconium oxide composite refractory material.
[0021] In a preferred embodiment of the present invention, the organic solvent is anhydrous ethanol.
[0022] In a preferred embodiment of the present invention, the mass ratio of the mixed powder, the ball milling medium and the ball milling beads is 1:3:3.
[0023] In a preferred embodiment of the present invention, the ball milling time is 12-24 hours.
[0024] In a preferred embodiment of the present invention, the pre-synthesized material is pressed into a sheet-like shape at 12-16 MPa for 3 min using a tablet press, and the synthesis is solid phase synthesis.
[0025] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:
[0026] 1. The raw materials for synthesizing the composite refractory material of the present invention are zirconium dioxide and barium carbonate, and the barium zirconium oxide composite refractory material is obtained through mixing, molding and sintering processes. The prepared barium zirconium oxide composite refractory material improves the refractoriness and density of the refractory material, reduces the apparent porosity, improves the compressive strength, and enhances the comprehensive performance by forming a composite barium-containing phase and a composite zirconium-containing phase;
[0027] 2. After the barium zirconium oxide grains are formed, the present invention is not easily corroded by the highly active alloy melt. At the same time, the element inclusions caused by the reaction between the crucible and the alloy melt no longer affect the composition of the molten alloy, thus avoiding uncontrollable products and reducing the dissolution of oxygen and metal elements in the composite material.
[0028] 3. The composite refractory material of the present invention has the advantages of stable chemical properties, high compressive strength, low thermal expansion coefficient, excellent thermal shock resistance, etc., and is widely used in the smelting of highly active metals.
[0029] 4. Patent CN201110350464.1 In the preparation of BaZrO3 refractory materials and crucibles for titanium alloy smelting, 0.5-5.0 mol% TiO2 needs to be added as a sintering aid. In the present invention, no additional sintering aid is needed. Adding excess BaCO3 can achieve the effect of sintering aid, and the process is simpler.
[0030] 5. Patent CN201110350464.1 discloses that when preparing BaZrO3 refractory materials and crucibles for titanium alloy smelting, pre-sintering at 800-1200°C for 4-10 hours is required, followed by sintering at 1650-1750°C for 5-10 hours.
[0031] According to the attached Figure 1 It can be seen from the phase diagram that the present invention only needs to be sintered at 1650-1700°C for 6-8h to obtain a dense and chemically stable multiphase refractory material, which greatly reduces energy consumption and time costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the phase diagram of ZrO2-BaO system.
[0033] Figure 2 The ratio of the raw materials for solid phase synthesis of Examples 1-3 of the present invention.
[0034] Figure 3 This is a microscopic morphology structure diagram of the solid phase synthesized crucible refractory material of Example 1 of the present invention.
[0035] Figure 4 This is a microscopic morphology structure diagram of the solid phase synthesized crucible refractory material of Example 2 of the present invention.
[0036] Figure 5 This is a microscopic morphology structure diagram of the solid phase synthesized crucible refractory material of Example 2 of the present invention.
[0037] Figure 6 This is a microscopic morphology diagram of the interface reaction between an embodiment of the present invention and a TiNi alloy. DETAILED DESCRIPTION
[0038] It can be seen from the phase diagram of the ZrO2-BaO system of the present invention that adding excessive BaO will not leave a single BaO phase in the refractory material, but will form a Ba2ZrO4+BaZrO3 dual-phase composite refractory material.
[0039] The novel refractory composite material of the present invention has a dense structure after forming a dual phase and is not easily corroded by a high-activity alloy melt. At the same time, the element inclusions brought by the reaction between the refractory material and the alloy melt no longer affect the composition of the molten alloy, thus avoiding uncontrollable products.
[0040] Therefore, the barium zirconium oxide composite refractory material of the present invention is a relatively stable crucible material, hardly reacts with active metals at high temperatures, has stable performance, and is a potential refractory material for smelting high-activity alloys.
[0041] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0042] Embodiment 1:
[0043] In this embodiment, a method for preparing a barium zirconium oxide composite refractory material adopts a staged solid phase synthesis method and has the following steps:
[0044] (1) Preparation of pre-synthetic materials:
[0045] The raw material components are calculated according to the molar percentage, and the ratio of each raw material is as follows: zirconium dioxide: barium carbonate = 1:1.2. An organic solvent is used as a ball milling medium. The mixed powder, ball milling medium and ball milling beads are added into a planetary ball mill in a mass ratio of 1:3:3. The mixed powder is wet-milled for 12 hours, and then the milled slurry is dried at 90-100°C for 18-24 hours. After drying, it is sieved to obtain a loose powder.
[0046] (2) Preparation of barium zirconium oxide composite refractory materials:
[0047] The powder was pressed into a sheet at 14 MPa for 3 minutes using a tablet press, and then sintered at 1650-1700°C for 6-8 hours using a solid phase synthesis method to obtain a barium zirconium oxide composite refractory material. Figure 3 The existence of two phases can be clearly observed, namely, the large-sized irregular polygonal BaZrO3 phase and the small-sized irregular spherical Ba2ZrO4 phase.
[0048] Experimental test analysis:
[0049] The crucible refractory material prepared in this example is applied to the smelting of TiNi alloy with equal atomic ratio. The smelting device is a WZG-2 vacuum induction furnace, and the temperature is recorded by a Marathon series two-color infrared thermometer. Vacuum is drawn before smelting, and argon is filled as a protective gas after the smelting starts. The specific operation is as follows:
[0050] A TiNi alloy with uniform composition is placed in the refractory crucible, and after being pumped down to 0.01Pa by a mechanical pump and a diffusion pump, argon gas is backfilled to 600Pa, during which the gas is purged and filled with argon gas for 5 times.
[0051] Control the power and heat at 20-30℃ / min to melt the TiNi alloy. Keep the temperature at 1450℃ for 3min, pour the molten alloy into the graphite crucible quickly, then stop heating and take out the inner wall of the crucible for characterization. Figure 6 It can be clearly seen that there is almost no reaction layer between the TiNi alloy and the refractory material.
[0052] The alloy cooled in the furnace was taken out, cut, polished, and the oxygen content of the alloy was tested by oxygen, nitrogen and hydrogen analyzer, and the zirconium content of the alloy was analyzed by ICP-AES inductively coupled atomic emission spectrometer. In the test results of the alloy, the oxygen content was less than 0.05wt% and the zirconium content was less than 0.02wt%. Both are far below the highest requirement for the use of medical titanium alloys (GB / T13810-2017).
[0053] Table 1 is the analysis results of oxygen content and zirconium content of the TiNi alloy smelted using the refractory crucible in Example 1:
[0054] Table 1
[0055] Melting times / times Oxygen content / wt% Zirconium content / wt% 1 0.0452 0.0068 2 0.0464 0.0170
[0056] In this embodiment, the barium oxide is derived from barium carbonate. The prepared barium zirconium oxide composite refractory material forms a composite barium-containing phase and a composite zirconium-containing phase to improve the density of the refractory material (density is 5.46 g / cm 2 ), mechanical strength and thermal shock resistance; after the barium zirconium oxide grains of this embodiment are formed, they are not easily corroded by the high-activity alloy melt.
[0057] At the same time, the element inclusions brought about by the reaction between the crucible and the alloy melt no longer affect the composition of the molten alloy, thus avoiding uncontrollable products and reducing the dissolution of oxygen and metal elements in the composite material.
[0058] The composite refractory material of this embodiment has stable chemical properties (Gibbs energy at 1500°C is -419 KJ / mol), low density (density is 5.46 g / cm 2 ), low thermal expansion coefficient (1.09×10 -5℃), excellent thermal shock resistance, etc., and can be used in the smelting of highly active metals.
[0059] Embodiment 2:
[0060] In this embodiment, a method for preparing a barium zirconium oxide composite refractory material adopts a staged solid phase synthesis method and has the following steps:
[0061] (1) Preparation of pre-synthetic materials:
[0062] The raw material components are calculated according to the molar percentage, and the ratio of each raw material is as follows: zirconium dioxide: barium carbonate = 1:1.5. An organic solvent is used as a ball milling medium. The mixed powder, ball milling medium and ball milling beads are added to a planetary ball mill in a mass ratio of 1:3:3. The ball milling is carried out by wet ball milling for 12 hours, and then the ball-milled slurry is dried at 90-100°C for 18-24 hours. After drying, it is sieved to obtain a loose powder.
[0063] (2) Preparation of barium zirconium oxide composite refractory materials:
[0064] The powder is pressed into sheets at 14 MPa for 3 minutes using a tablet press, and then sintered at 1650-1700° C. for 6-8 hours using a solid phase synthesis method to obtain a barium zirconium oxide composite refractory material.
[0065] In microstructure Figure 4 The existence of two phases can be clearly observed, namely, the large-sized irregular polygonal BaZrO3 phase and the small-sized irregular spherical Ba2ZrO4 phase.
[0066] In the test results of the alloy, the oxygen content is less than 0.05wt% and the zirconium content is less than 0.02wt%, both of which are far lower than the highest requirement for medical titanium alloy use standards (GB / T13810-2017).
[0067] In this embodiment, after the barium zirconium oxide grains are formed, they are not easily corroded by the highly active alloy melt. At the same time, the element inclusions caused by the reaction between the crucible and the alloy melt no longer affect the composition of the molten alloy, thus avoiding uncontrollable products and reducing the dissolution of oxygen and metal elements in the composite material.
[0068] The composite refractory material of this embodiment has stable chemical properties (Gibbs energy at 1500°C is -423KJ / mol), low density (density is 5.52g / cm 2 ), low thermal expansion coefficient (6.67×10 -6 ℃), excellent thermal shock resistance, etc., and can be used in the smelting of highly active metals.
[0069] Embodiment 3:
[0070] In this embodiment, a method for preparing a barium zirconium oxide composite refractory material adopts a staged solid phase synthesis method and has the following steps:
[0071] (1) Preparation of pre-synthetic materials:
[0072] The raw material components are calculated according to the molar percentage, and the ratio of each raw material is as follows: zirconium dioxide: barium carbonate = 1:1.7. An organic solvent is used as a ball milling medium. The mixed powder, ball milling medium and ball milling beads are added into a planetary ball mill in a mass ratio of 1:3:3. The mixed powder, ball milling medium and ball milling beads are wet-milled for 12 hours. The milled slurry is then dried at 90-100°C for 18-24 hours and sieved after drying to obtain a loose powder.
[0073] (2) Preparation of barium zirconium oxide composite refractory materials:
[0074] The powder is pressed into sheets at 14 MPa for 3 minutes using a tablet press, and then sintered at 1650-1700° C. for 6-8 hours using a solid phase synthesis method to obtain a barium zirconium oxide composite refractory material.
[0075] In microstructure Figure 5 The existence of two phases can be clearly observed, namely, the large-sized irregular polygonal BaZrO3 phase and the small-sized irregular spherical Ba2ZrO4 phase.
[0076] In the test results of the alloy, the oxygen content is less than 0.05wt% and the zirconium content is less than 0.02wt%, both of which are far lower than the highest requirement for medical titanium alloy use standards (GB / T13810-2017).
[0077] After the barium zirconium oxide grains are formed, they are not easily corroded by the highly active alloy melt. At the same time, the element inclusions caused by the reaction between the crucible and the alloy melt no longer affect the composition of the molten alloy, thus avoiding uncontrollable products and reducing the dissolution of oxygen and metal elements in the composite material. The composite refractory material of this embodiment has stable chemical properties (Gibbs energy at 1500℃ is -416KJ / mol), low density (density is 5.11g / cm 2 ), low thermal expansion coefficient (2.5×10 -6 ℃), excellent thermal shock resistance, etc., and can be used in the smelting of highly active metals.
[0078] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention of the present invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.
Claims
1. A method for preparing a barium zirconium oxide composite refractory material, characterized in that: The steps are as follows: (1) Preparation steps of pre-synthetic material: The zirconium dioxide and barium carbonate are mixed to obtain a mixed powder, an organic solvent is used as a ball milling medium, the mixed powder, the ball milling medium and the ball milling beads are added into a planetary ball mill in a mass ratio of 1-2:3-4:3-4, and ... mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder, the mixed powder (2) Preparation steps of barium zirconium oxide composite refractory material: The powder of step (1) is pressed into a sheet at 12-16 MPa using a tablet press, and then sintered at 1650-1700° C. for 6-8 hours to obtain a barium zirconium oxide composite refractory material; In the mixed powder, the raw material composition ratio is calculated by mole percentage as follows: Zirconium dioxide: barium carbonate = 1:1.2-1:2; The barium zirconium oxide composite refractory material is a two-phase coexistence composite phase of BaZrO3 phase and Ba2ZrO4 phase; The size of the BaZrO3 phase is greater than that of the Ba2ZrO4 phase; The BaZrO3 phase is in an irregular polygonal state, and the Ba2ZrO4 phase is in a spherical particle state.
2. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The specific size range of the BaZrO3 phase is 3.5-6.0 μm.
3. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The specific size range of the Ba2ZrO4 phase is 1.0-2.5 μm.
4. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The organic solvent is anhydrous ethanol.
5. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The mass ratio of the mixed powder, the ball milling medium and the ball milling beads is 1:3:
3.
6. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The ball milling time is 12-24h.
7. The method for preparing a barium zirconium oxide composite refractory material according to claim 1, characterized in that: The pre-synthesized material is pressed into a sheet-like shape at 12-16 MPa for 3 minutes using a tablet press, and the synthesis is solid phase synthesis.
8. A barium zirconium oxide composite refractory material, characterized in that: The barium zirconium oxide multiphase refractory material is prepared by the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
BaZrO3 refractory material for smelting titanium alloy and preparation method of crucibles
CN102503489A
Preparation method of multiphase ceramic filter and product
CN117923944A